Association Between Perceived Levels of Stress and Self-Reported Food Preferences Among Males and Females: A Stated Preference Approach Based on the China Health and Nutrition Survey - Yang, Fahui; Li, Ruonan; Ren, Xiaojian; Cao, Bing; Gao, Xiao (Frontiers in Public Health, 2022)
Objective: Stress is a major public health challenge and is associated with undesirable eating behaviour. This cross-sectional study aimed to explore whether there is an association between perceived level of stress and food preference among Chinese adults. Study design: Perceived level of stress was measured using the Chinese version of the 14-item Perceived Stress Scale, whereas self-reported food preferences were investigated by means of ﬁve food classiﬁcation questions, including questions regarding the consumption of fast food, salty snacks, fruit, vegetables, and soft/sugary drinks. Methods: The data were collected from the 2015 China Health and Nutrition Survey. Information of 8,216 adults (≥18 years) on perceived level of stress, self-reported food preferences, and other important covariates was available and analysed. Results: Perceived level of stress was negatively associated with a preference for fruit (β= -0.58, 95% CI: -0.81 to -0.34, p<0.0001) and vegetables (β= -1.13, 95% CI: -1.41 to -0.85, p<0.0001), while it was positively associated with a preference for fast food (β= 0.36, 95% CI: 0.08 to 0.64, p=0.011) and soft/sugary drinks (β= 0.48, 95% CI: 0.30 to 0.66, p<0.0001) after adjusting for potential confounders. No association between a preference for salty snacks and perceived level of stress was found in either men or women. Conclusions: The present population-based study reported strong associations between perceived level of stress and self-reported food preferences among Chinese adults. Sex differences related to this association were also worthy of attention.